Analisis Rencana Induk Sistem Penyediaan Air Minum (RISPAM) Kota Makassar Tahun 2023-2043 - Madaul, Rahful Ahmad; Hilmansyah, Hilmi; Ibal, La (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The provision of drinking water is a basic need that is essential to improve people's welfare. Makassar City, as a metropolitan city, faces significant challenges in ensuring adequate availability of clean water, especially with increasing population growth and changing environmental conditions. Data from 2022 shows that 24.13% of Makassar's population still experiences water scarcity, which is exacerbated by the high water loss of 52% in the distribution of the PDAM system. In response, the Makassar City Government has prepared a master plan for the drinking water supply system (RISPAM) for the 2023-2042 period to ensure sustainable SPAM development that is integrated with the regional spatial plan. This study uses the arithmetic projection method; water demand analysis includes population growth projections, water loss in distribution, and estimates of per capita needs. Data from various PDAM service areas are also analyzed to understand the characteristics of different needs. The results of the study indicate that the population of Makassar City in 2043 is projected to reach 1,530,631 people, with water needs reaching 4,898.02 liters per second in 2033 and 297.02 liters per second in 2043. The potential of groundwater in Tamalate and Tamalanrea, as well as the main river flow, provides opportunities for the development of additional raw water sources. However, high water loss and low access to clean water are major challenges that require mitigation efforts through efficient distribution systems and optimal utilization of water resources. This study emphasizes the importance of integrating spatial planning and water resource management for the sustainability of the water supply system in Makassar City.